ГЕОПОЛИТИКИЙН ОНОЛ БА МОНГОЛ УЛСЫН ӨНӨӨГИЙН БАЙДЛЫГ ЗАДЛАН ШИНЖЛЭХ НЬ - Н.Галиймаа (Politology, 2023)
The collapse of socialist system had opened new era of Mongolian democratic foreign policy, because of beginning of liberal multipolar policy in the world. Thankful to the “open door” foreign policy Mongolia has receiving economic aid and political support from donor countries, which is giving little chance to play own game in the international arena. One of biggest achievement of Mongolian government during last 23 years, is Mongolia has been becoming from undeveloping country to developing country, because the country is rich in terms of mineral resources, with major coal reserves and significant deposits of copper, gold, fluorspar and tungsten. Development of the raw materials sector can lead to substantial growth and widespread prosperity for the population as a whole. But, geopolitical interest of developed countries such as USA is focusing on neighboring countries of Mongolia; China and Russia, which have huge territory and population. There are two reasons, which are making Mongolian game in international arena vulnerable to others. - Mongolia is landlocked country, strategically located between China and Russia (both have regional geopolitical code and both have ambiguous goal to become super power within global code), - Mongolia has no sea-outlet, therefore possibility to penetrate regional and global transportation networks is very limited. Therefore, Mongolia should have liberal policy for continuing economic aid and political support of developed countries, except of dominance realpolitik in international arena last decade of XXI century. Author had attempt in her article to make analysis on geopolitical volatility of Mongolia, within few contemporary theories of geopolitics.